Trends in pharmaceutical waste management as an important element of pharmaceutical safety - Pankevych, Ostap (Annals of Mechnikov's Institute, 2025)
Introduction. Pharmaceutical waste (PhW), when released into the environment, poses risks to the human body and other biological species and poses a challenge to the pharmaceutical safety of the state. The aim of the work. To investigate the status and prospects of PhW management as an important element of pharmaceutical safety. Materials and Methods. The work used general scientific methods: content analysis, abstraction, interpretation and generalization. The materials selected were 30 scientific publications obtained from the electronic databases Google Scholar and PubMed, a guideline from the FIP/WHO, five European and five Ukrainian regulatory documents, as well as Eurostat statistical data and corporate information from a foreign research and analytical company and four domestic pharmaceutical enterprises and public organizations. Results. Analyzing the risks posed by uncontrolled accumulation of PhW, as well as the volume of the global market for its management, the importance of proper management of PhW as a basic element of pharmaceutical safety is highlighted. The achievements of Ukrainian scientists on the issue of PhW management are shown. The global nature of the problem of household PhW and the peculiarities of their management in Europe and Ukraine are indicated. It presents current views on PhW management that are aligned with the European Green Deal, the European Strategic Approach to Pharmaceuticals in the Environment, and the Pharmaceutical Strategy for Europe. Considering the importance of the circular economy, Ukrainian innovative technology is described using the example of paracetamol, which will contribute to reducing the negative impact on the environment and increasing the efficiency of PhW management. It is shown that an important task is the harmonization of national legislation with European regulatory documents in the field of PhW management. Attention is paid to the need to develop a national concept on this. Conclusions. Based on the theoretical generalization of scientific research, international guidelines, European and Ukrainian regulatory documents, as well as statistical and corporate information, the article shows contradictory trends in the management of PhW, including household PhW, as an important component of pharmaceutical safety, as well as the significant problems of this management in Ukraine. Based on the multifaceted nature and complexity of PhW and the need to ensure an adequate level of pharmaceutical safety in the state, the issue of developing a national concept of PhW management on the basis of harmonizing national legislation with European legislation is updated and its eight main theses are identified. Key words: pharmaceutical waste, medicine, management, pharmaceutical safety, utilization, national concept.